Pengaruh Metode Simulasi Terhadap Pengetahuan dan Keterampilan Pertolongan Pertama Pada Kejang Pada Anak di Desa Kutakerangan Kecamatan Simpang Kanan Kabupaten Aceh Singkil Provinsi Aceh Tahun 2024 - Kismiasih Adethia; Elis Noviana; Lisa Putri Utami Damanik; Diah Pitaloka; Debby Chyntia Yun (Pusat Riset dan Inovasi Nasional, 2024)
The impact that can occur when parents do not immediately provide first aid for febrile seizures is that it can increase the risk of damage to the brain, delays in development and the emergence of symptoms of epilepsy. Parents should know information regarding the treatment that needs to be given to children who experience febrile seizures. Because if parents have a minimal attitude and do not immediately take their child to a health worker, it will cause the child to experience the effects of febrile seizures, one of which is brain damage and death. The aim of this research is to analyze the influence of simulation methods on knowledge and skills of first aid for seizures in children in Kutakerangan Village, Simpang Kanan District, Aceh Singkil Regency, Aceh Province in 2024. The type of this research is Quasy Experimental Research with a one group pretest-posttest research design which consists of 1 experimental group carried out in Kutakerangan Village. The population in this study were mothers who had babies aged 0-12 months, totaling 33 respondents. The sampling technique used is Total Sampling. As well as bivariate analysis using the Wilcoxon test. In conclusion, the p-value was obtained: 0.00 <0.05, which means there is an influence between knowledge and first aid on seizures and the p-value: 0.003 <0.05 means there is an influence between skills and first aid on seizures in Kutakerangan Village, Simpang Kanan District, Aceh Singkil Regency, Aceh Province in 2024.